2011
DOI: 10.23907/2011.027
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Cardiac Conduction System in the Investigation of Sudden Unexpected Death

Abstract: When a gross and microscopic autopsy, drug screen, and past medical history fail to yield a cause of death, the forensic pathologist may opt to study the cardiac conduction system. This paper describes the excision of the SA (sinoatrial) node and AV(atrioventricular) node-containing areas of the heart and the microscopic appearance of normal SA and AV nodes, His bundle and bundle branches. Conduction system findings that have been reported to be significant include fibromuscular hyperplasia (often mislabeled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We think that it may be a result of the differences between the regional dietary habits as well as the higher average age in our study (2,(12)(13)(14)28 (12,13,18,29 (4,13,(30)(31)(32)(33)(34) (14,21,(42)(43)(44) (2,13,16,26,27,46 …”
Section: Methodsmentioning
confidence: 78%
“…We think that it may be a result of the differences between the regional dietary habits as well as the higher average age in our study (2,(12)(13)(14)28 (12,13,18,29 (4,13,(30)(31)(32)(33)(34) (14,21,(42)(43)(44) (2,13,16,26,27,46 …”
Section: Methodsmentioning
confidence: 78%
“…Once thought to be mesothelial in origin, they are now considered to be endodermal rests and the term “mesothelioma” is no longer used. Histologically, these tumors consist of variable-sized cysts lined with cuboidal, transitional, or squamous cells in a background of dense fibrosis (Image 51) (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…It is typified by nonatherosclerotic luminal narrowing of this small artery by intimal and medial thickening (Image 54). Several studies have concluded that severe (>75%) narrowing of the AV nodal artery is significant enough to explain sudden cardiac death, with a proposed mechanism of AV nodal ischemia (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…After excision, serial sections perpendicular to the tricuspid annulus should be made. 12 Trichrome stain is highly recommended to better appreciate the cardiac conduction system.…”
Section: Discussionmentioning
confidence: 99%